diff --git a/library/data/list/basic.lean b/library/data/list/basic.lean index 4b80a1ce5..24f6366e7 100644 --- a/library/data/list/basic.lean +++ b/library/data/list/basic.lean @@ -43,10 +43,8 @@ theorem append_nil_right : ∀ (t : list T), t ++ nil = t theorem append.assoc : ∀ (s t u : list T), s ++ t ++ u = s ++ (t ++ u) | append.assoc nil t u := rfl | append.assoc (a :: l) t u := - begin - change a :: (l ++ t ++ u) = (a :: l) ++ (t ++ u), - rewrite append.assoc - end + show a :: (l ++ t ++ u) = (a :: l) ++ (t ++ u), + by rewrite (append.assoc l t u) /- length -/ @@ -83,10 +81,8 @@ theorem concat_cons (x y : T) (l : list T) : concat x (y::l) = y::(concat x l) theorem concat_eq_append (a : T) : ∀ (l : list T), concat a l = l ++ [a] | concat_eq_append nil := rfl | concat_eq_append (b :: l) := - begin - change b :: (concat a l) = (b :: l) ++ (a :: nil), - rewrite concat_eq_append - end + show b :: (concat a l) = (b :: l) ++ (a :: nil), + by rewrite concat_eq_append -- add_rewrite append_nil append_cons @@ -140,10 +136,8 @@ theorem head_cons [h : inhabited T] (a : T) (l : list T) : head (a::l) = a theorem head_concat [h : inhabited T] (t : list T) : ∀ {s : list T}, s ≠ nil → head (s ++ t) = head s | @head_concat nil H := absurd rfl H | @head_concat (a :: s) H := - begin - change head (a :: (s ++ t)) = head (a :: s), - rewrite head_cons - end + show head (a :: (s ++ t)) = head (a :: s), + by rewrite head_cons definition tail : list T → list T | tail nil := nil @@ -309,17 +303,14 @@ theorem map_cons (f : A → B) (a : A) (l : list A) : map f (a :: l) = f a :: ma theorem map_map (g : B → C) (f : A → B) : ∀ l : list A, map g (map f l) = map (g ∘ f) l | map_map nil := rfl | map_map (a :: l) := - begin - rewrite [▸ (g ∘ f) a :: map g (map f l) = _, map_map l] - end + show (g ∘ f) a :: map g (map f l) = map (g ∘ f) (a :: l), + by rewrite (map_map l) theorem len_map (f : A → B) : ∀ l : list A, length (map f l) = length l | len_map nil := rfl | len_map (a :: l) := - begin - rewrite ▸ length (map f l) + 1 = length l + 1, - rewrite (len_map l) - end + show length (map f l) + 1 = length l + 1, + by rewrite (len_map l) definition foldl (f : A → B → A) : A → list B → A | foldl a nil := a @@ -375,7 +366,8 @@ definition unzip : list (A × B) → list A × list B theorem unzip_nil : unzip (@nil (A × B)) = (nil, nil) -theorem unzip_cons (a : A) (b : B) (l : list (A × B)) : unzip ((a, b) :: l) = match unzip l with (la, lb) := (a :: la, b :: lb) end +theorem unzip_cons (a : A) (b : B) (l : list (A × B)) : + unzip ((a, b) :: l) = match unzip l with (la, lb) := (a :: la, b :: lb) end theorem zip_unzip : ∀ (l : list (A × B)), zip (pr₁ (unzip l)) (pr₂ (unzip l)) = l | zip_unzip nil := rfl @@ -393,7 +385,7 @@ end combinators end list -attribute list.decidable_eq [instance] +attribute list.decidable_eq [instance] attribute list.decidable_mem [instance] attribute list.decidable_any [instance] attribute list.decidable_all [instance]